Diversity and Dissemination of Brettanomyces bruxellensis During Winemaking and Barrel Aging - Sturm, Maria Elena; Chimeno, Selva Valeria; González, Magalí Lucía; Lerena, María Cecilia; Rojo, María Cecilia; Becerra, Lucía Maribel; Mercado, Laura Analia; Combina, Mariana (MDPI, 2025)
Brettanomyces bruxellensis is recognized as the main spoilage yeast in red wines, producing volatile phenols that negatively impact wine quality. However, few studies have investigated strain diversity within wineries. Understanding the diversity and distribution of B. bruxellensis strains in different wines can provide insights into the origin and timing of contamination. This study aimed to evaluate the presence and diversity of B. bruxellensis biotypes during the production of four red wines in the same winery and to identify critical contamination stages. The analysis covered the entire process, from grape to six months of aging. B. bruxellensis yeasts were isolated and identified, and representative strains were typified by RAPD analysis. The results suggest that B. bruxellensis contamination did not originate from a single source. The grapes harbored low levels of B. bruxellensis, yet all wines were positive before barrel filling. This study demonstrates that winery equipment can serve as a vector for Brettanomyces introduction. Two critical contamination stages were identified: the shared use of equipment during fermentation, facilitating strain dissemination across wines, and the reuse of barrels, introducing new strains during aging. Additionally, some winery practices further promote B. bruxellensis spread and proliferation